عہد ِ بنو عباس میں کتب ِ دلائل النبوۃ کا اِرتقاء : ایک تجزیہ - Jahangir Asif; Muhammad Riaz Mahmood (Pakistan Journal of Islamic Research)
The Muslim scholars laid the foundation of the science of biography (sira). Research was conducted on the different aspects of the Prophet of Islam (peace and blessings be upon him) which was preserved in books. The Muslim scholars in the period of Banu Abbas played a major role in the development of this science. The books authored in this period compiled the miracles of the Messenger (peace and blessings be upon him), and they refuted objections by those who did not believe in their verity. The lofty position of Prophethood was described by writers; also, they repudiated the demurrals raised by the Greeks. Because the believing savants contributed extensively to the Islamic literature, their intellectual efforts carry great import. The present research paper highlights the efforts of the scholars with regard to promoting Islamic science in the Abbasid period.